EXPLORING SHARING TIME INTEGRATION IN EFL CLASSROOM FOR YOUNG LEARNERS - Amalul Umam; Kristiyantini Kristiyantini (Universitas Lambung Mangkurat, 2021)
Abstract: There are still many schools in Indonesia that use the one-way communication learning system. It made students feel bored and monitored. Therefore teachers need a pleasant learning atmosphere and a learning system that can build interactive relationships between teachers and students. One of them is by doing sharing time activities in the learning process. This research is conducted to determine the purpose, benefits, and scope of sharing time using a quantitative descriptive approach—the data collected by conducting informal observations and interviews. Validity and reliability observed several times. The technique used to analyze is Miles and Huberman's model. From this study, it was found that the purpose of sharing time is to see the students' understanding of a topic, and to practice the ability of students speaking in front of the audience. Benefits for students, (1) Trained to express ideas or experiences. (2) Improve student vocabulary. (3) Learn to compose correct sentences. Benefits for teachers, (1) Build communication between teachers and students. (2) Make the teacher able to know the abilities of the students. (3) The teacher gets exciting ideas from students. (4) Helping teachers to have a closer relationship with students. Constraints (1). Topics that are not yet familiar make students hesitate. (2). Limited Time